Infliximab in Recalcitrant Generalized Pustular Arthropatic Psoriasis - Serrão, V (2013)
Generalized pustular psoriasis is an unstable inflammatory type of psoriasis, with widespread areas of erythema and sterile pustules, associated with fever and systemic symptoms. Infliximab is a monoclonal antibody with anti-TNFalpha activity, approved for use in psoriasis. We describe a male patient with a long history of stable arthropathic psoriasis, hospitalized with a generalized pustular psoriasis and acute exacerbation of articular complaints. The disease was resistant to multiple therapies (acitretin, methotrexate and corticosteroids), so the patient was started on infliximab, with a very rapid response of both cutaneous and articular symptoms. He had complete clearing of lesions at week 12, and marked improvement of the articular symptoms. No recurrence occurred at 8 months of follow-up with infliximab every 8 weeks. Infliximab had an extremely rapid therapeutic action response on a recalcitrant generalized pustular psoriasis. The articular response was also excellent, with significant improvement of quality of life.